2015
DOI: 10.1002/2014gl062971
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification along the 24.5°N section in the subtropical North Atlantic

Abstract: Ocean acidification is directly related to increasing atmospheric CO 2 levels due to human activities and the active role of the global ocean in absorbing part of this anthropogenic CO 2 . Here we present an assessment of the pH changes that have occurred along 24.5°N in the subtropical North Atlantic through comparison of pH observations conducted in 1992 and 2011. It reveals an overall decline in pH values in the first 1000 dbar of the water column. The deconvolution of the temporal pH differences into anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
(84 reference statements)
1
9
0
Order By: Relevance
“…The standard deviations of the C ant estimates are rather similar to those from other regions where C ant has been compared across many cruises (i.e. 2.4 µmol kg −1 in the South Atlantic Ocean, Ríos et al (2003); 2.7 µmol kg −1 in the equatorial Atlantic Ocean, 24 • N, Guallart et al (2015); and 2.7 µmol kg −1 reported from a transect along the western boundary of the Atlantic Ocean from 50 • S to 36 • N, Ríos et al, 2015). The standard deviations of the mean values of the Iberian Abyssal Plain samples across all (last row of Table 2) were taken as an estimate of the reproducibility of the methodologies.…”
Section: Trend Uncertaintysupporting
confidence: 72%
See 2 more Smart Citations
“…The standard deviations of the C ant estimates are rather similar to those from other regions where C ant has been compared across many cruises (i.e. 2.4 µmol kg −1 in the South Atlantic Ocean, Ríos et al (2003); 2.7 µmol kg −1 in the equatorial Atlantic Ocean, 24 • N, Guallart et al (2015); and 2.7 µmol kg −1 reported from a transect along the western boundary of the Atlantic Ocean from 50 • S to 36 • N, Ríos et al, 2015). The standard deviations of the mean values of the Iberian Abyssal Plain samples across all (last row of Table 2) were taken as an estimate of the reproducibility of the methodologies.…”
Section: Trend Uncertaintysupporting
confidence: 72%
“…Overall this change can be explained as the result of the contraction of the subpolar gyre that took place since the mid-90s (e.g. Flatau et al, 2003;Häkkinen and Rhines, 2004;Böning et al, 2006). Wakita et al (2013) also found lower-than-expected acidification rates in the surface waters of the Pacific Ocean, which they explained as being the consequence of increasing A T .…”
Section: Water Mass Acidification and Driversmentioning
confidence: 92%
See 1 more Smart Citation
“…The first potentiometric pH Spanish measurements were done in 1977 during the GALICIA IV cruises, but it was only after the slow introduction of more precise spectrophotometric techniques (see section 1.2) that pH data collection on repeat hydrographic sections started in the early 1990s. However, no pH data were included in the first oceanographic data global consistency exercise, the Global Ocean Data Analysis Project (GLODAP); , only 40% of the total data included pH in Carbon in the North Atlantic (CARINA) data product; and only 31% included pH data in the second GLODAP data product. , As a consequence, estimates of water column OA ascribed to anthropogenic input are generally indirectly derived avoiding the use of direct pH measurements. , As discrete and sensor-based (e.g., Ion Sensitive Field Effect Transistor, ISFET, , electrodes) pH measurements become more widespread, it is essential to ensure high quality calibrations and intercomparability among different observational platforms, from ships to new technologies (e.g., gliders and Argo floats).…”
Section: Introductionmentioning
confidence: 99%
“…However, these data do not reveal the change in ocean pH on a longer multidecadal time scale. Considering this limitation of the ocean carbon chemistry data, several studies have attempted to estimate E d-anth to understand the long-term change in ocean pH (Byrne et al, 2010;García-Ibáñez et al, 2016;Guallart et al, 2015;Ríos et al, 2015;Wakita et al, 2017Wakita et al, , 2013. However, their results showed that the rates of pH decrease were significantly different from those expected between the atmosphere and ocean with an increase in atmospheric anthropogenic CO 2 and implied a crucial role of E i-anth on ocean acidification.…”
Section: Introductionmentioning
confidence: 99%